Produção cultural no movimento Steampunk: a saga fantástica em Santa Maria (RS) - Rocha, Rebeca Genildes Peneluc (2023)
Steampunk became popular in the 1980s, extrapolating the time-space of the novel, taking the literary movement to the streets, to other aesthetic dimensions, aligning itself with entertainment and consumer culture. Coming from fantastic literature, the Steampunk subgenre manifests itself in the widest possible way, being received in several countries around the world, generating different types of cultural products, through social actions, forming and diversifying identity groups. Steampunk, also known as vaporpunk, assumes a retrofuturistic style, in which thousands of followers adhere to their Victorian clothing, artifacts and other ritualistic gestures to produce their scenes, as well as other creative performances. Based on this, the research entitled: "Cultural Production in the Steampunk movement: The fantastic saga in Santa Maria, RS", linked to the research line Archival Documentary Heritage, of the Professional Master in Cultural Heritage of the Federal University of Santa Maria (UFSM), aims to make known part of the cultural production in the Steampunk movement and fantastic literature in Santa Maria (RS). For this purpose, the study focused on broadening the discussion about the Steampunk aesthetic, first, identifying it as a subgenre of fantastic literature; second, as a cultural movement, bringing the discussion about the importance of the movement in society, its repercussion in specific events and contexts; and third, the description of the product generated from the study, namely, the "Steampunk Glossary", an illustrated material with the main words linked to the Steampunk aesthetic, for the purpose of knowledge of the general public. The Glossary is an instrument that disseminates culture, acting as an extralinguistic tool that transmits multiple information, including ideological information. For the development of this research, data collection was used, consultation in the research portals of postgraduate works, bibliographic and documentary survey, through books and other materials related to the subject. Thus, as a method of data collection, the technique of applying a questionnaire was developed in order to show the strategies and procedures of the writers mobilize the Steampunk movement, in recent years, in the city of Santa Maria (RS). Data analysis was performed through content analysis of the responses of these writers. The research revealed the cultural mediation between the Steampunk aesthetic and the people who promote the movement through their artistic practices. It also revealed the importance of literature as an agent of knowledge and culture in the moral, personal and intellectual formation of individuals who appropriate it, and the Glossary created as a product of this dissertation is a means of initial access to the Steampunk universe.